Application of combined technique of surface electron microscopy and crystal structure analysis in the identification and traceability of unknown samples - Li, Shuang (AIP advances, 2025)
This paper introduces an innovative technique that combines electron microscopy with crystal structure analysis to systematically identify and trace the origins of samples with unknown compositions, milligram-level sizes, and suspected to be horn. Four types of animal tissues were selected as control samples. Through this combined analysis, we gathered multimodal characteristic information, including microscopic morphology, elemental composition, crystal structure, and in situ electron beam-induced deformation, for comparative analysis. The data analysis reveals that the four-dimensional characteristics of the unknown sample differ significantly or partially from the hoof and horn tissues of bovine animals and the dentin in animal teeth but closely match the dentin of porcine tusks. This suggests that the unknown sample originates from porcine tusks or tusks of terrestrial mammals homologous to porcine. The technique offers three innovative advantages: (1) it preserves the original micro-nano scale structure of the sample through non-destructive multimodal analysis; (2) the four-dimensional feature map allows precise fingerprint identification of microgram-level solid samples; and (3) it overcomes the limitations of traditional analysis methods. This technique provides novel methodological support for identifying and tracing biological materials in fields such as cultural heritage identification, forensic evidence analysis, and endangered species protection, demonstrating significant interdisciplinary application potential.